(untitled) (Iranian Journal of Kidney Diseases, 2011)
Introduction. Carotid intima-media thickness (CIMT) has been introduced as a cardiovascular disease predictor which may increase in hamodialysis patients. As there are many risk factors in the uremic state that theoretically lead to increase in CIMT, this study was aimed to determine risk factors of CIMT increase in a group of hemodialysis patients. Materials and Methods. Seventy-two hemodialysis patients with a mean age of 61.3 ± 15.0 years and 49 individuals with no history of chronic disease (control group) underwent ultrasonography for measurement of CIMT. Correlation of demographic, clinical, and laboratory factors with CIMT was studied. Carotid intima-media thickness was measured by one radiologist in the bilateral common carotid artery, and the mean value of the two sides was reported. Results. The mean duration on dialysis was 82.4 ± 78.0 months. The mean CIMT was 0.96 ± 0.25 mm (range, 0.4 to 1.7 mm) in hemodialysis patients and 0.76 ± 0.06 mm (range, 0.58 to 0.91 mm) in the control group (P < .001). The mean CIMT was significantly higher in men compared to women on dialysis and in diabetic compared to nondiabetics patients. There was a positive correlation between CIMT and age (r = 0.266, P = .02) and serum cholesterol (r = 0.375, P = .002). No correlation was found between CIMT and other studied variables. Conclusions. Carotid intima-media thickness was greater in hemodialysis patients compared to the control group. It was mainly affected by traditional cardiovascular risk factors and uremic risk factors did not specifically affect CIMT.